Interfacial contributions to perpendicular magnetic anisotropy in Pd/Co2MnSi/MgO trilayer films. (13th April 2016) - Fu, Huarui; You, Caiyin; Li, Yunlong; Wang, Ke; Tian, Na
Abstract: Heusler alloy Co2 MnSi is widely selected as the ferromagnetic layer to achieve a giant tunneling magnetic resistance (TMR). It is also one of the most promising materials for potential spintronic applications of magnetic random access memory (MRAM) due to the high spin polarization, in which the configuration of perpendicular magnetic anisotropy (PMA) possesses great advantages over the in-plane ones. Therefore, it is highly desirable to investigate the PMA effects of the Co2 MnSi layer with a suitable stack structure. In this work, a strong PMA (1.61 × 10 6 erg cm −3 ) is demonstrated in the system of Pd/Co2 MnSi/MgO trilayer films. The contributions of the interfaces beside the ferromagnetic Co2 MnSi layer were quantitatively clarified. The interfacial anisotropy K s, MgO of 0.79 erg cm −2 at the Co2 MnSi/MgO interface is larger than the K s, Pd value of 0.26 erg cm −2 at the Pd/Co2 MnSi interface. Due to the dual interfacial effects, the strong PMA can be sustained at the high annealing temperature with a thick Co2 MnSi layer of about 4.9 nm, which is favorable to the potential spintronic application. The Mn–O bonding was also found to be enriched at the Co2 MnSi/MgO interface for the annealed Pd/Co2 MnSi (3.4 nm)/MgO film with the large PMA, showing an experimental evidence for the theoretical results of the Mn–O bonding contribution to PMA.